-7=(x+6)-6x

(x-2) (3x-3)

5x -2(x-2) = 6 -2(-3x-3)

5x -2x +4 = 6 +6x +6 (use the distributive property)

3x + 4 = 6x + 12 (collect terms)

4 = 3x + 12 (subtract 3x from both sides to get all x on one side)

-8 = 3x (subtract 12 from both sides to get only x on one side)

-8/3 = x (divide both sides by 3 to get x by itself)

Check

5(-8/3) -2((-8/3)-2) = 6 - 2(-3(-8/3)-3)

-40/3 -2(-8/3-6/3) = 6 - 2(8-3)

-40/3 -2(-14/3) = 6 -2(5)

-40/3 + 28/3 = 6 - 10

-12/3 = -4 (yes)

5x -2x +4 = 6 +6x +6 (use the distributive property)

3x + 4 = 6x + 12 (collect terms)

4 = 3x + 12 (subtract 3x from both sides to get all x on one side)

-8 = 3x (subtract 12 from both sides to get only x on one side)

-8/3 = x (divide both sides by 3 to get x by itself)

Check

5(-8/3) -2((-8/3)-2) = 6 - 2(-3(-8/3)-3)

-40/3 -2(-8/3-6/3) = 6 - 2(8-3)

-40/3 -2(-14/3) = 6 -2(5)

-40/3 + 28/3 = 6 - 10

-12/3 = -4 (yes)

5x-2x+4=3x+4=-36

3x=-32

3x=-32

(x-2)/3-(x+5)/6=(5x-2)/9

(5x/2x-6)+(x+2/3-x)=

5x-2(x-2)=6-2(-3x-3)

5x-2x+4=6+6x+6

3x+4=6x+12

3=3x+12

-9=3x

x=-3

5x-2x+4=6+6x+6

3x+4=6x+12

3=3x+12

-9=3x

x=-3

5x-2+4=6+6x+6

5x+2=6x+12

5x-6x=12+(-2)

-x=10 or x=-10

5x+2=6x+12

5x-6x=12+(-2)

-x=10 or x=-10